2022
DOI: 10.5812/erms-122572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Medical Students' Satisfaction with the Virtual Assessment of Cardiac Physiology Course

Abstract: Background: Universities have switched to virtual assessments due to the spread of COVID-19 around the world. Therefore, this study aimed to evaluate the satisfaction level of medical students at the Abadan University of Medical Sciences (AUMS) with the virtual assessment methods of the cardiac physiology course. Methods: This study was conducted on 42 medical students of AUMS who were in the second semester of 2020 - 2021 (COVID-19 pandemic) and participated in the cardiac physiology course. Researchers devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Online practical examination such as telecommunication technology simulation can be an effective strategy to assess clinical skills competencies and provides personalised effective and immediate feedback to students [ 47 , 54 ]. Furthermore, it is suggested that online evaluation had benefits and expected impacts on student and teacher happiness and performance during the COVID-19 pandemic [ 63 ], and also improved the teaching and learning process both in managing distance education, increasing class size and staff workload [ 48 , 50 ]. Despite the concerns that included unfamiliarity and limited virtual assessment experience and the insufficient number of information technology technicians that interferes with proper digitalisation [ 48 ], the convenience of virtual clinical assessment including the removal of travelling to examination centres provides opportunity to partake at the comfort of both students and the examiners’ homes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Online practical examination such as telecommunication technology simulation can be an effective strategy to assess clinical skills competencies and provides personalised effective and immediate feedback to students [ 47 , 54 ]. Furthermore, it is suggested that online evaluation had benefits and expected impacts on student and teacher happiness and performance during the COVID-19 pandemic [ 63 ], and also improved the teaching and learning process both in managing distance education, increasing class size and staff workload [ 48 , 50 ]. Despite the concerns that included unfamiliarity and limited virtual assessment experience and the insufficient number of information technology technicians that interferes with proper digitalisation [ 48 ], the convenience of virtual clinical assessment including the removal of travelling to examination centres provides opportunity to partake at the comfort of both students and the examiners’ homes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%